Turkmen Literacy and Turkmen Identity before the Soviets: the Ravnaq al-Islām in Its Literary and Social Context - Frank, Allen J. (Journal of the economic and social history of the Orient, 2020)
Abstract Despite assertions of almost universal illiteracy among pre-Revolutionary Turkmens, an examination of the widely popular maktab primer, the Ravnaq al-Islām, shows that literacy among Turkmens before 1917 was substantially higher than previously thought. Additionally, the work and legends surrounding it show us Turkmen maktab texts contributed to a sense of supra-tribal Turkmen identity, which has generally been discounted or ignored in previous studies of Turkmen social history.